O desafio de Aparecida. Uma configuração eclesial para a América Latina - Miranda, Mário de França (Revista eclesiástica brasileira, 2009)
The Aparecida Document represents a challenge for the Church. It asks for a change in mentality (a pastoral conversion) on everyone’s part. However, the required missionary ardour will only become true if it finds appropriate structures for its realization. The text starts off in the context of a historical ecclesial configuration that still remains in the imagination of many Catholics despite all the novelties of the Vatican II Council. Next, it distinguishes theological identity from the institutional configuration of the Church; it shows the significance of the local church for a truly experienced faith; and it confronts the challenge set by the Episcopal Conference in Aparecida. In a final section it presents three characteristics of a missionary Church: a Church of mystics, one of missionary Christians and one of the poor.